2020
DOI: 10.1021/acs.analchem.9b05627
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for Global Profiling and Identification of 2- and 3-Hydroxy Fatty Acids in Plasma by UPLC–MS/MS

Abstract: 2-Hydroxy fatty acids (2-OHFAs) and 3-hydroxy fatty acids (3-OHFAs) with the same carbon backbone are isomers, both of which are closely related to diseases involving fatty acid oxidation disorder. However, the comprehensive profiling of 2- and 3-OHFAs remains an ongoing challenge due to their high structure similarity, few structure-informative product ions, and limited availability of standards. Here, we developed a new strategy to profile and identify 2- and 3-OHFAs according to structure-dependent retentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Furthermore, a metabolomics study which utilised urinary samples from SCC patients and healthy controls demonstrated oesophageal SCC was associated with alterations in fatty acid β-oxidation and the metabolism of purines, amino acids, and pyrimidines 23 . These studies amongst others highlight the importance of metabolic alterations in oesophageal cancer compared to healthy controls and highlight the potential for biomarker development for disease diagnosis and progression 24,25 . It would be of interest to employ a similar approach in OAC treatmentnaïve tumour tissue across the various stages of disease progression to further elucidate the role of altered energy metabolism in OAC and compare the findings to real-time metabolic analysis.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, a metabolomics study which utilised urinary samples from SCC patients and healthy controls demonstrated oesophageal SCC was associated with alterations in fatty acid β-oxidation and the metabolism of purines, amino acids, and pyrimidines 23 . These studies amongst others highlight the importance of metabolic alterations in oesophageal cancer compared to healthy controls and highlight the potential for biomarker development for disease diagnosis and progression 24,25 . It would be of interest to employ a similar approach in OAC treatmentnaïve tumour tissue across the various stages of disease progression to further elucidate the role of altered energy metabolism in OAC and compare the findings to real-time metabolic analysis.…”
Section: Discussionmentioning
confidence: 97%
“…The extracted ion chromatograms (EIC) and their CID mass spectra of representative species from each class were shown in Figure 1. In general, the saturated and less unsaturated FAs (FA 24:0, m/z 367) loose a molecule of water to produce a most significant ion (m/z 349) (Figure 1a) whereas, HFAs (FAOH 24:0, m/z 383) (Figure 1b) commonly, loses m/z 46 to produce its characteristic ion (m/z 337) in their mass 21,22 . However, the polyunsaturated fatty acids predominately lose a molecule of CO2 rather than H2O to give the most significant ion in their spectra 23 .…”
Section: Identification Of Fatty Acids and Derivativesmentioning
confidence: 99%
“…The ultrasound assisted extraction (UAE) could be one of the most suitable techniques [23], as it is very simple to use, requires relatively inexpensive apparatus, reduces the volume of solvent [24], uses acoustic energy and solvents to enhance the release and diffusion of phenolic compounds from various matrices [25], and allows to use green extraction solvents with a high efficiency due to the mechanical effects that it produces in the cellular structure of the matrix [26,27]. Many analytical methods have been used to determine phenolic compound contents in fruit peel, but currently only UPLC-MS/MS could provide higher sensitivity, selectivity, shorter analysis time, and simultaneous determination of many phenolic compounds [28]. Therefore, in the study, we first proposed to use UPLC-MS/MS combining with ultrasonic extraction to simultaneous determine the main phenolic compound contents in banana peel and further explored the difference of phenolic compound contents in banana peel of different cultivars and subgroups with different levels of maturity.…”
Section: Introductionmentioning
confidence: 99%